Dampak Pertambangan Emas Tradisional Terhadap Perubahan Sosial Ekonomi Masyarakat Di Gampong Mersak Kecamatan Kluet Tengah Kabupaten Aceh Selatan - Edi Farlan; Indra Indra; Ahmad Humam Hamid (Jurnal Ilmiah Mahasiswa Pertanian, 2016)
During the existence of the traditional gold mining in the Mersak Village subdisdtrict of Central Kluet district South Aceh has been a lot changes in local community life. The research methodology used is descriptive method with qualitative approach. Data collection techniques used were interviews, observation, and literature study. Informants in this study consisted of village officials, community leaders and the community of gold miners. Data analysis technique used is the technique of interactive analysis by Milles and Huberman form of data reduction, data presentation and verification / conclusions. The results of the research tells us that the existence of gold mines in the Village Ruin has an impact on the social and economic condition of the community. Negative impact on the gold mining aspects of uncontrolled population movements and worrying, the incidence rate is increasing conflict and transition people's livelihood of farmers to miners who create agricultural infrastructure is not functioning optimally. Also, positive impact on the gold mining aspects of the comprehensive work opportunities for people and rising incomes that can be seen from the high purchasing power. Keywords: Mining, Impact, Social, Economic